Use of Concrete Media for Mathematics Lesson in Elementary School - Ratnasari Widyastuti (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This article as a literature review aims to find out the importance of concrete media in learning mathematics for first grade students at SD Negeri 01 Sringin. Mathematics is a basic science that is used to solve problems in various fields of science. Most students think that learning mathematics is difficult and boring learning. The world of children is synonymous with an atmosphere full of joy. And joy is usually expressed through play with concrete or tangible objects. Children need a relaxed and fun atmosphere in learning. This is what finally makes the writer find an effective way to make it easier and more interesting for students to learn mathematics. Namely by demonstrating interesting concrete objects.